2022
DOI: 10.3389/fpsyg.2022.959979
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in physical education: The role of cognitive factors and self-efficacy

Abstract: Among the beliefs related to teaching work, self-efficacy stands out and encourage innovation across the global education systems. Specifically, the lack of interest among instructors in introducing innovative techniques in physical education is a concern across China. Therefore, this study intends to investigate the role of cognitive indicators (mental workload, decision-making process, innovation in physical education, and self-efficacy) of innovation in physical education across China. This study opted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Past experiences, performances, and psychological states are all factors that influence selfefficacy beliefs. (Li, Xu & Zhao, 2022;Schunk, 1984). Selfefficacy is emphasized in motivation theories as a fundamental condition (Deci & Ryan, 2012).…”
Section: The Relationship Between Self-efficacy Beliefs and Achieveme...mentioning
confidence: 99%
“…Past experiences, performances, and psychological states are all factors that influence selfefficacy beliefs. (Li, Xu & Zhao, 2022;Schunk, 1984). Selfefficacy is emphasized in motivation theories as a fundamental condition (Deci & Ryan, 2012).…”
Section: The Relationship Between Self-efficacy Beliefs and Achieveme...mentioning
confidence: 99%
“…Germane cognitive load increases schema construction, therefore promoting the execution of the task [12,13]. Broad evidence has shown that self-efcacy also afects an individual's cognitive load [14,15]. Jiang et al [14] reported that self-efcacy in English reading among students is negatively related to intrinsic cognitive load.…”
Section: Introductionmentioning
confidence: 99%